(3GdCeGdj GdTLQjIs - (3GHf GdTLQj , gHI Gddg Hf Ydj Hf eMeO GdMSfj, CHh GdSYGOGJ,J (B542 (3g` s ((3CSYO Hf eYGdi Hf EHQGgje Hf YHOGddg s)
(3ChdgG (B:s
(3GdeLdS Gdehai GdNeSjf s
(3GdfSNI GdNGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B427 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B162s
Keywords: (3GdCOHs